Remarkably distinct mechanical flexibility in three structurally similar semiconducting organic crystals studied by nanoindentation and molecular dynamics - Devarapalli, Ramesh; Kadambi, Sourabh Bhagwan; Chen, Chun-Teh; Krishna, Gamidi Rama; Kammari, Bal Raju; Buehler, Markus J.; Ramamurty, Upadrasta; Reddy, C. Malla (Chemistry of Materials, 2019)
Distinct macroscopic mechanical responses of the three crystals of naphthalene diimide derivatives, 1Me, 1Et, and 1nPr, studied here are very intriguing because their molecular structures are very similar, with the difference only in the alkyl chain length. Among the three crystals examined, 1Me shows highly plastic bending nature, 1Et shows elastic flexibility, and 1nPr is brittle. A detailed investigation by nanoindentation and molecular dynamics (MD) simulations allowed us to correlate their distinct mechanical responses with the way the weak interactions pack in crystal structures. The elastic modulus (E) of 1Me is nearly an order of magnitude lower than that of 1Et, whereas hardness (H) is less than half. The low values of E and H of 1Me indicate that these crystals are highly compliant and offer a low resistance to plastic flow. As the knowledge of hardness and elastic modulus of molecular crystals alone is insufficient to capture their macroscopic mechanical deformation nature, that is, elastic, brittle, or plastic, we have employed three-point bending tests using the nanoindentation technique. This allowed a quantitative evaluation of flexibility of the three mechanically distinct semiconducting molecular crystals, which is important for designing larger-scale applications; these were complemented with detailed MD simulations. The elastic 1Et crystals showed remarkable flexibility even after 1000 cycles. The results emphasize that the alkyl side chains in functional organic crystals may be exploited for tuning their self-assembly as well as their mechanical properties. Hence, the study has broad implications, for example, in crystal engineering of various flexible, ordered molecular materials.